2022
DOI: 10.3389/fgene.2022.852165
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Analysis of the Growth Hormone Transgenic Female Triploid Atlantic Salmon (Salmo salar) Hepatic Transcriptome Reveals Broad Temperature-Mediated Effects on Metabolism and Other Biological Processes

Abstract: This study examined the impact of rearing temperature (10.5, 13.5 or 16.5°C) on the hepatic transcriptome of AquAdvantage Salmon (growth hormone transgenic female triploid Atlantic salmon) at an average weight of 800 g. Six stranded PE libraries were Illumina-sequenced from each temperature group, resulting in an average of over 100 M raw reads per individual fish. RNA-sequencing (RNA-seq) results showed the greatest difference in the number of differentially expressed transcripts (1750 DETs), as revealed by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…Prolonged exposure to elevated temperatures could lead to acclimatory responses, thus limiting the requirement for heat shock proteins to prevent protein damage or denaturation. Although, 800 g AquAdvantage Salmon reared in freshwater at 16.5°C for several months still exhibited higher expression of hsp90ab1 and serpinh1 and lower expression of cirbp compared to salmon reared at 10.5°C [ 54 ]. The differences in time spent at elevated temperatures, genetic background, water salinity, ploidy, and/or transgenesis make it difficult to directly compare with past results [ 54 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Prolonged exposure to elevated temperatures could lead to acclimatory responses, thus limiting the requirement for heat shock proteins to prevent protein damage or denaturation. Although, 800 g AquAdvantage Salmon reared in freshwater at 16.5°C for several months still exhibited higher expression of hsp90ab1 and serpinh1 and lower expression of cirbp compared to salmon reared at 10.5°C [ 54 ]. The differences in time spent at elevated temperatures, genetic background, water salinity, ploidy, and/or transgenesis make it difficult to directly compare with past results [ 54 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…RT-qPCR Study and Analysis. Seven genes of interest were chosen based on past studies that have shown them to be responsive to chronic heat stress in Atlantic salmon liver [53,54]. Several heat shock proteins [i.e., hsp70, hsp90aa1, hsp90ab1, and serpinh1 (alias hsp47)] were selected alongside transcripts associated with oxidative stress (i.e., cirbp, ndufa1, and ucp2).…”
Section: Overall Experimental Design and Fishmentioning
confidence: 99%
See 3 more Smart Citations